Magnetic resonance imaging of athlete's heart: myocardial mass, left ventricular function, and cross-sectional area of the coronary arteries - Zandrino, F.; Molinari, G.; Smeraldi, A.; Odaglia, G.; Masperone, M. A.; Sardanelli, F. (European Radiology, 2000)
To evaluate left ventricular myocardial mass and function as well as ostial coronary artery cross-sectional area in endurance athletes, an athlete group of 12 highly trained rowers and a control group of 12 sedentary healthy subjects underwent MR examination. An ECG-gated breath-hold cine gradient-echo sequence was used to calculate myocardial mass, end-diastolic and end-systolic volumes, stroke volume, and cardiac output, all related to body surface area, as well as ejection fraction. A 3D fat-saturated ECG- and respiratory-triggered navigator echo sequence was used to evaluate coronary arteries: left main (LM), left anterior descending (LAD), left circumflex (LCx), and right coronary artery (RCA). Cross-sectional area was calculated and divided for body surface area. Myocardial mass was found significantly larger in athlete group than in control group (p = 0.0078), the same being for end-diastolic volume (p = 0.0078), stroke volume (p = 0.0055), LM (p = 0.0066) and LAD (p = 0.0129). No significant difference was found for all the remaining parameters. Significant correlation with myocardial mass was found for LM (p < 0.001) and LAD (p = 0.0340), not for LCx and RCA. Magnetic resonance imaging is a useful tool in evaluating the myocardial hypertrophy and function of athlete's heart. Magnetic resonance angiography is a valuable noninvasive method to visualize the correlated cross-sectional area increase of the left coronary artery system.